PENGARUH KARAKTERISTIK INFORMASI SISTEM AKUNTANSI MANAJEMEN, KETIDAKPASTIAN LINGKUNGAN, DAN DESENTRALISASI TERHADAP KINERJA MANAJERIAL (STUDI EMPIRIS PADA PERUSAHAAN BUMN DI BANDA ACEH) - Rizka Febrianti; Yulia Fitri (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2019)
The purpose of this research is to examine the effect of characteristics of management accounting system information, environmental uncertainty, and decentralization on managerial performance. Data collection techniques in this study were collected by distributing questionnaires to 70 managers who had been set as samples in 18 BUMN companies in Banda Aceh. Statistical tests are performed using multiple linear regression analysis with SPSS 20. The results of the study prove that the four characteristics of management accounting information systems (broad scope, timeliness, aggregation, integration), and decentralization have a positive and significant effect on managerial performance. Enviromental uncertainty have a negative and significant effect on managerial performance.